2022
DOI: 10.1186/s40708-022-00170-8
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy seizure prediction with few-shot learning method

Abstract: Epileptic seizures prediction and timely alarms allow the patient to take effective and preventive actions. In this paper, a convolutional neural network (CNN) is proposed to diagnose the preictal period. Our goal is for those epileptic patients in whom seizures occur late and it is very challenging to record the preictal signal for them. In the previous works, generalized methods were inevitably used for this group of patients which were not very accurate. Our approach to solve this problem is to provide a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several algorithms have been proposed to evaluate the effectiveness of transfer learning in seizure prediction 11 , 16 , 28 , 29 , 43 . These studies reported improved performance and computational efficiency, consistent with the findings of this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several algorithms have been proposed to evaluate the effectiveness of transfer learning in seizure prediction 11 , 16 , 28 , 29 , 43 . These studies reported improved performance and computational efficiency, consistent with the findings of this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the DCAE being trained on data from a different database with distinct acquisition systems, it was evident that the models benefited from using pretrained weights. Several algorithms have been proposed to evaluate the effectiveness of transfer learning in seizure prediction 11,16,28,29,43 . These studies reported improved performance and computational efficiency, consistent with the findings of this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation